Investigation of asphalt mixture internal structure consistency in accelerated discrete element models. (30th May 2020) - Zhou, Xiaodong; Chen, Siyu; Ge, Dongdong; Jin, Dongzhao; You, Zhanping
Highlights: This study proposed a set of equations to calculate a material modulus reduction range, that is used to accelerate the discrete element method (DEM) simulation of asphalt mixture compaction and meanwhile maintain simulation accuracy. A three-step compaction process was proposed to compare the specimens. The results exhibited the DEM simulation agreed with the laboratory results for specimens of three gradation designs under three compaction states. Internal structure indexes in respect of specimen's height, rotation angles of coarse aggregates, and spatial distribution of mastic particles were proposed to evaluate the effects of the reduced material modulus. Abstract: The discrete element method (DEM) requires an enormous amount of computational resources when applied to asphalt mixture simulation. Reducing material modulus is recognized as an efficient method to cut down the computational cost. However, over-reduced material modulus would case unacceptable calculation errors for DEM models, and the allowable modulus reduction range is not clear. Based on the small displacement assumption in the DEM modeling, the overlap ratio between particles should be small enough to ensure efficient force transition and discrete system stability. Combining this assumption with time step determination and force-displacement law, a theoretical inference that specified a material modulus reduction range without causing an exceeded overlap ratio can be derived. To verify this theoretical inference, a three-step DEM compaction model, including gravity fall, static compaction, and gyratory compaction processes was established for asphalt mixtures. Three groups of asphalt mixtures with different mixture designs were tested both in the laboratory and in simulation. To evaluate the effects of the reduced material modulus on the internal-structure of asphalt mixture specimen under three compaction states, this study proposed 4 categories of internal-structure indexes in respect of specimen's height, average coordination number, rotation angles of coarse aggregates, and spatial distribution of mastic particles. In the presented case, when the modulus reduction was 1/100 times, the maximum simulation error of internal-structure indexes (except the average coordinate number) was around 4% compared to the control group. Meanwhile, the model's calculation efficiency was increased by 8–10 times depending on the mixture design.